Change Management – Condition of Organizational Sustainability in IT&C Small and Medium-Sized Enterprises - Dan Popescu; Alina Ciocârlan-Chitucea; Alexandra Steriu; Cristina State (Amfiteatru Economic)
The present research aims to establish and outline strategies for promoting change in the context of organizational learning, in order to maintain deeply active and creative human resources, while capable of achieving economic sustainability. This is becoming more obvious now as the changes take place in a dynamic world where human resources are the only key factors able to provide the design and implementation of routine changes and procedures, in the present and not in the future. Furthermore, to highlight strengths and weaknesses of approaches regarding the sustainability and organizational change, our topic of research was conducted as an empirical study on the IT&C Small and Medium-sized Enterprises (SMEs), especially in the context of sustainability tending to become even more a value of modern, dynamic and powerful organizations. The main objective of the article is to outline some potential ways to implement the change management in the IT&C Romanian SMEs environment and their perception manner concerning the rationality and operationality of change, to ensure the viability and the organizational sustainability.